Mentally impaired persons' performance evaluation using an e-mail programme: a follow up study. - Pereira LM; Saragoça E; Loura LC; Espadinha C (Technology & Disability, 2004)
This paper presents a follow up study of the analysis of eight users' performance along the ALDICT project. Users were classified concerning communication and computer usage in three different levels (high, medium and low). Each participating country chose 6 Mentally Impaired users, 2 from each level. In order to characterize their performance concerning communications and computer skills, an observation methodology was developed and data was collected in four different project moments. Results showed an improvement concerning computer usage and communication skills. The programme created the possibility to use different types of graphic signs. However, it seems that the e-mail programme did not become part of the users' everyday life as a distance communication tool.